Analisis Pengaruh Variasi Slice Thickness Terhadap Kualitas Citra Pemeriksaan CT Scan Urografi Pada Kasus Nefrolitiasis Di RS TK. II Pelamonia Makassar - Ni Putu Rita Jeniyanthi; Cokorda Istri Ariwidiastuti; I Bagus Gede Dharmawan; Tripaldy Battola Toding (Lembaga Pengembangan Kinerja Dosen, 2024)
Background: Kidney stones (nephrolithiasis) are solid masses formed from urine precipitated crystals. The formation of stones is caused by increased calcium, oxalate and uric acid content in the body, scans to view kidney stones (nephrolithiasis) can be performed with or without contrast. Non-contrast CT urography is the imaging modality of choice for the initial evaluation of patients with suspected urolithiasis, as it has a sensitivity of up to 98% and specificity of 96-98%. Components that affect image quality in CT scans are spatial resolution, contrast resolution, and noise. One of the important parameters in image quality is the selection of slice thickness. Spatial resolution is the ability to show objects or organs with a high level of contrast. Noise is the standard deviation percentage of the sum of pixel values obtained from the waterbath image. Methods; This type of research is quantitative research with an experimental approach to analyze the effect of slice thickness variations on image quality using variations of 2 mm, 3 mm, 4 mm, 5 mm, and 6 m. The data were collected in August 2023 with 10 samples. Data were collected in August 2023 with 10 samples. Researchers took urographic CT scan examination data with a diagnosis of nephrolithiasis. Results and Conclusion: With the results of the research conducted, it can be concluded that in the overall Friedman test results there is an effect of using slice thickness variations on image quality in urographic CT Scan examinations with nephrolithiasis diagnoses. using slice thickness variations. Based on the results of this study, the researcher can recommend on CT Scan urography with nephrolithiasis diagnosis using 4 mm slice thickness to get good and optimal image quality results.